ABCG5/G8 Deficiency in Mice Reduces Dietary Triacylglycerol and Cholesterol Transport into the Lymph. Issue 4 (13th February 2015) - Zhang, Linda S.; Xu, Min; Yang, Qing; Lou, Danwen; Howles, Philip N.; Tso, Patrick
Abstract: The adenosine triphosphate‐binding cassette (ABC) transporter G5/G8 is critical in protecting the body from accumulating dietary plant sterols. Expressed in the liver and small intestine, it transports plant sterols into the biliary and intestinal lumens, thus promoting their excretion. The extent to which G5/G8 regulates cholesterol absorption remains unclear. G5/G8 is also implicated in reducing the absorption of dietary triacylglycerols (TAG) by unknown mechanisms. We hypothesized that G5/G8 suppresses the production of chylomicrons, and its deficiency would enhance the absorption of both dietary TAG and cholesterol. The aim of this study was to investigate the effects of G5/G8 deficiency on lipid uptake and secretion into the lymph under steady‐state conditions. Surprisingly, compared with wild‐type mice (WT) ( n = 9), G5/G8 KO ( n = 13) lymph fistula mice given a continuous intraduodenal infusion of [3H]‐TAG and [14C]‐cholesterol showed a significant ( P < 0.05) reduction in lymphatic transport of both [ 3 H]‐TAG and [ 14 C]‐cholesterol, concomitant with a significant ( P < 0.05) increase of [ 3 H]‐TAG and [ 14 C]‐cholesterol accumulated in the intestinal lumen. There was no difference in the total amount of radiolabeled lipids retained in the intestinal mucosa between the two groups. G5/G8 KO mice given a bolus of TAG showed reduced intestinal TAG secretion compared with WT, suggesting an independent role for G5/G8 in facilitating intestinal TAG transport. Our data demonstrate that G5/G8 deficiency reduces the uptake and secretion of both dietary TAG and cholesterol by the intestine, suggesting a novel role for the sterol transporter in the formation and secretion of chylomicrons.